Insect Infestation at the Nursery Level of Terminalia arjuna (Roxb. Ex DC.) in Punjab - Pandha, Y. S.; Saini, M. S.; Dargan, J. S. (Indian Forester, 2006)
It was explored that 35 insects species were infesting in overlapping manner the seedlings of Terminalia arjuna, starting from germination till transplanting in field, in the forest nurseries in Punjab. Among these there were highest number of Hemipterans (12) followed by Orthopterans (8), Coleopterans (6), Lepidopterans (6) and three as insect visitors. Out of these thirty four are new host records from Punjab whereas twenty-eight are new host records from India.